PENGARUH SIKAP WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM PROVINSI BALI: PERAN ADOPSI E-FORM SEBAGAI PEMEDIASI - Mas Patni Widyasari, Ida Ayu Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
The contribution rate of micro, small and medium enterprises (MSMEs) to Gross Domestic Product (GDP) is 62%. However, this is not in line with the contribution of MSMEs to Indonesia's tax ratio. Indonesia's tax ratio target in 2024 only 9.95% to 10.20% is still lower than the target in 2022.  So it can be said that tax compliance is still low. The purpose of this study is to test whether the e-form system can mediate the impact of taxpayer attitudes on tax compliance. The population of MSMEs in Bali Province is 439,382. The minimum sample calculation uses the Slovin formula with an error tolerance of 5% and the minimum sample is 400. This study uses primary data collected by distributing questionnaires to respondents online through Google Form media. The analysis method uses Path Analysis with the help of the SPSS 26.0 application and for testing mediating variables using the Sobel test. The findings in this study state if the taxpayer's attitude towards tax compliance has a positive and significant effect, e-form adoption towards tax compliance has a positive and significant effect, the taxpayer's attitude towards e-form adoption has a positive and significant effect, and e-form adoption can mediate taxpayer attitudes towards tax compliance.